lncRNA ATXN8OS promotes breast cancer by sequestering miR-204 - Deng, Zhen (Mol Med Rep, 2019)
Breast cancer (BC) is a common malignancy among women and the leading cause of female cancer mortality worldwide. In recent years, increasing evidence has shown that long non-coding RNAs (lncRNAs) can act as competing endogenous RNAs (ceRNAs) in human cancer and that they are involved in many biological processes, including proliferation, migration, apoptosis and invasion. In the present study, the biological function and molecular mechanism of ataxin 8 opposite strand (ATXN8OS) in BC tissue and cell lines were investigated. It was found that ATXN8OS was markedly up-regulated in BC tissue and cell lines, and that its level of overexpression was inversely linked with the overall survival rate of patients with BC. Knockdown of ATXN8OS inhibited proliferation, viability and invasion in the human MCF7 and MDA-MB-231 BC cell lines. In addition, microRNA-204 (miR-204) was negatively associated with the expression of ATXN8OS in BC tissues and cell lines. A luciferase assay demonstrated a direct binding site for miR-204 within ATXN8OS, and inhibition of miR-204 stimulated the tumour-promoting effect of ATXN8OS on BC cells. In conclusion, the present study suggested that ATXN8OS acts as a tumour promoter by sequestering miR-204 during the development of BC, therefore providing a mechanistic insight which may facilitate the diagnosis and treatment of BC.